Interferons in human inborn errors of disease - Laurel Stine; Sara Cahill; Fiachra Humphries (mBio)
ABSTRACT Interferons are ubiquitously produced cytokines with diverse cellular functions. IFNs play essential functions in responding to viral infections and tumorigenesis by initiating an interferon-stimulated gene response and triggering the adaptive immune response. However, excessive, prolonged IFN production disrupts cellular homeostasis and can lead to an array of severe inflammatory conditions. Due to developments in whole genome sequencing and elucidation of key signaling pathways, excessive IFN production and its associated interferon-stimulated gene expression signature is now an established molecular diagnostic of Mendelian inborn errors in immunity termed “interferonopathies.” In addition, identification of Mendelian loss-of-function mutations in critical mediators of the IFN response has been identified as the causal factors of immune deficiencies and susceptibility to viral infections. Thus, IFNs and their preceding signaling pathways now represent major therapeutic targets. In this review, we outline the existing evidence on the role IFNs play in human disease and the genetic mechanisms that underlie excessive IFN production or immune deficiencies.